Wife's Divorce Lawsuit and Husband's Rejection of Khuluq in the Perspective of Islamic Law - Masri Masri (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
This article explores the phenomenon of a wife filing for divorce against her husband and the rejection of khulʿ (mutual divorce) from the perspective of Islamic law. Using a normative juridical approach and textual analysis of Qur'anic verses, hadiths, and scholars' opinions, it explains the conditions under which a wife may seek divorce, the mechanism of khulʿ, and the circumstances in which khulʿ may be rejected. The study findings reveal that Islam provides space for women to uphold their rights while emphasizing the importance of justice, responsibility, and consultation in resolving marital conflicts.